The Effect of Light Difference and Feed that Provided to Improve The Quality of Fish Colour, Growth and Survival rate for Platy Fish (Xiphophorus helleri) - Ari Fahriza; Hamdan Alawi; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted from May 16 until July 4 2016 in the fish hatchery and breeding laboratory, Fisheries and Marine Sciences Faculty of Riau University. The purpose of this study was to determine the influence of light (dark, light, sunlight) and the type of feed (Tubifex sp and pellet) on colour quality, growth and survival rate Platy fish (Xiphophorus helleri). Experimental method used in this study was completely randomized design with factorial 3 x 2 x 3. The first factor was light consist of dark light, bulb light and sun, while the second factor was type food (Tubifex sp. feed and TAKARI pellet) with three replications. The fish was reared in 3 L aquarium those reared with dark and bulb light were dow inside and that with sun light was dow outside.The result showed that the best treatment from that all is to giving sunlight and feed the platy with Tubifex sp and the sunlight given TAKARI Pellet feed can improve the colour quality till level 30 of sunlight level. Treatment with feed Tubifex sp provide the absolute best length of 2.40 cm and the fish weights from the absolute best in sun light treatments with feed Tubifex sp can increase to 0.34 g. The Best survival rate in treatment without light / dark, sunlight, lamplight with feed Tubifex sp and sunlight, lamplight with Pellet feed TAKARI of 94.44%. and for the Results of water quality measurements: temperature ranging from 26.1 to 31.3 ° C, pH range between 6.6 to 7.3 and DO ranged from 4.2 to 6.3 ppm.Key word: the colour quality of fish, Xiphophorus helleri, Growth, Survival Rate